Influence of Innovative Pedagogical Approaches (IPA) on Academic Achievement of Pre-Service Mathematics Teachers in Colleges of Education in Oyo State - Sabitu Abiodun; Omenihu George ODUALI (Academic Bright Collaboration, 2026)
Purpose - This study examines why innovative pedagogical approaches are necessary in mathematics education, particularly to address persistent gaps in academic achievement among pre-service mathematics teachers. It aims to determine the extent to which such approaches improve learning outcomes and whether gender plays a significant role in shaping achievement.Methods – A pre-test and post-test quasi-experimental design was adopted. The population comprised 173 pre-service mathematics teachers in Colleges of Education in Oyo State, with intact classes of 200-level students selected through total enumeration. Data were collected using a self-structured Mathematics Achievement Test, validated by experts, with a reliability coefficient of 0.88 (KR-25). Data analysis was conducted using Analysis of Variance (ANOVA) and multiple regression at a 0.05 significance level.Findings – Results show a significant effect of innovative pedagogical approaches on academic achievement (F(1,172)=122.216; p<0.05). Gender did not show a statistically significant influence despite a high F-value (F(1,172)=103.402; p>0.05). Jointly, innovative pedagogy and gender significantly predicted achievement (F(2,171)=81.084; Adj R²=0.494; p<0.05), explaining 49.4% of the variance.Research implications – The study is limited by its quasi-experimental design and focus on a specific regional context, which may restrict generalizability. The use of intact classes may also introduce uncontrolled variables affecting internal validity.Originality – This study provides empirical evidence quantifying the impact of innovative pedagogy on pre-service teacher achievement. It highlights the limited role of gender and emphasizes the need for structured pedagogical reform, suggesting future research should explore longitudinal effects and broader contexts.